1980
DOI: 10.1093/schbul/6.3.506
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Psychophysiology in Early Onset Psychosis

Abstract: Research on psychophysiological functioning in early onset psychosis is reviewed within the context of etiological formulations stressing perceptual and selective attention abnormalities. Electroencephalographic (EEG) measures, including resting EEG level, alpha blocking, average evoked response, and contingent negative variation, have received most attention in the literature; cardiovascular and electrodermal indices have not been so extensively explored in this group of children. While the nature of differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 125 publications
2
13
0
Order By: Relevance
“…Nevertheless, some authors (James & Barry, 1980) have recently suggested that early onset psychosis and schizophrenia have in common an abnormal neurophysiological reactivity to stimuli expressed in the activity of phasic autonomic response mechanisms. Our findings support these speculations: Autistic children and schizophrenics at least show a remarkable resemblance in the way they respond electrodermally to auditive stimuli of moderate intensity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, some authors (James & Barry, 1980) have recently suggested that early onset psychosis and schizophrenia have in common an abnormal neurophysiological reactivity to stimuli expressed in the activity of phasic autonomic response mechanisms. Our findings support these speculations: Autistic children and schizophrenics at least show a remarkable resemblance in the way they respond electrodermally to auditive stimuli of moderate intensity.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review, James and Barry (1980) conclude that no characteristic of CNS functioning can be unequivocally related to infantile autism; the single trend to emerge from the data is that children suffering from this syndrome show responses that are different from those of normal children. The nature and direction of these differences can only be surmised.…”
mentioning
confidence: 99%
“…Although there are a few firsthand reports from high-functioning persons with autism about the impact of stress on their lives (Grandin & Scariano, 1986;Williams, 1992), traditional paper-and-pencil tests or interviews are often limited in usefulness with this population because of their deficits in communication (James & Barry, 1980).…”
Section: Measuring Stress In Autism and Other Developmental Disabilitiesmentioning
confidence: 99%
“…Early studies suggested, on the one hand (Bernal, 1965;Bernal & Simmons, 1969), that autistic children were hyperresponsive and slower to habituate and, on the other (Bernal & Miller, 1971), that physiological responsivity was diminished and correlated with behavioral unresponsiveness. More recent studies (James & Barry, 1980b have indicated reduced habituation rates of electrodermal responses and respiratory pause to both simple visual stimuli and auditory tones, with enhanced responding of cephalic and peripheral vasculature and larger skin conductance and peripheral pulse amplitude responses in autistic children, as compared with normal and retarded controls. Their results suggest major abnormalities in the psychophysiological reactivity of autistic children.…”
Section: Introductionmentioning
confidence: 99%